Anisotropic magnetization, critical temperature, and paramagnetic Curie temperature in the highly anisotropic magnetic Heusler compound Rh2CoSb - He, Yangkun; Sibille, Romain; Chen, Dong; Kroder, Johannes; Helm, Toni; Schnelle, Walter; Felser, Claudia; Fecher, Gerhard H. (Physical Review B, 2021)
The paramagnetic Curie temperature θp is a concept that describes the magnetic ordering temperature in the well-established Curie-Weiss law. Despite the successful explanations of the magnetic behavior, the anisotropy is not usually considered. Although anisotropic θp has been reported for several layered antiferromagnetic or ferrimagnetic materials owing to the orientation-dependent exchange, in ferromagnetic systems, θp was thought to be almost isotropic for decades, and the occasionally reported small difference has remained unexplained. In this paper, we experimentally report the anisotropic magnetization, critical temperature, and paramagnetic Curie temperature in highly anisotropic magnetic Rh2CoSb caused by a large magnetocrystalline anisotropy. The saturation magnetization along the c axis is 25% larger than that along the a axis. The critical temperature and paramagnetic Curie temperature along the c axis are 6 and 15 K higher than those along the a axis, respectively, as deduced from the Arrott plots and inverse susceptibility. A simple modification of the Curie-Weiss law was made to calculate the anisotropic θp, which well explains not only Rh2CoSb, but also many other previously reported ferromagnetic materials.
CRIS-Team Scopus Importer:2022-04-14